Self-reported sexual and psychosocial health among non-heterosexual Danes. Issue 3 (May 2015) - Graugaard, Christian; Giraldi, Annamaria; Frisch, Morten; Falgaard Eplov, Lene; Davidsen, Michael
Introduction : Little is known about the sexual and psychosocial health of non-heterosexual Danes. Based on a large population study, the aim of this article was to compare quality-of-life-related key variables of heterosexual and non-heterosexual men and women, aged 16–66. Materials and methods : Cross-sectional data from the nationwide, representative Health and Morbidity Survey ( n = 8496) were used to compare variables concerning both general and sexual well-being of self-identified heterosexual and non-heterosexual respondents. Results : Nearly twice as many non-heterosexual than heterosexual men rated their sexual life as bad or very bad (22.5% versus 12.8%), while no statistical difference was seen among women (13.6% versus 10.6%). For both genders, significantly more non-heterosexuals than heterosexuals stated that their sexual needs were not met (17.9% versus 7.7% for men and 14.8% versus 6.9% for women), and significantly more non-heterosexuals reported acts of sexual violence (8.3% versus 2.1% for men and 35.8% versus 13.0% for women). Finally, non-heterosexual respondents had contemplated suicide more than twice as often as heterosexuals (15.9% versus 7.4% for men and 19.7% versus 8.3% for women). Actual suicide attempts were roughly three times more frequent in the non-heterosexual groups (8.3% versus 2.6 % for men and 11.8% versus 4.2% for women). Conclusions : Overall, non-heterosexual Danes reported higher degrees of sexual and/or psychosocial distress than heterosexuals. Further research is needed; but scientists, clinicians and public health workers should be aware that non-heterosexuals may pose specific health-related challenges and requirements.